A protocol for low contamination risk of autologous serum drops in the management of ocular surface disorders. Issue 4 (18th March 2004) - Lagnado, R; King, A J; Donald, F; Dua, H S
Abstract : Aim: To assess microbial contamination of 20% autologous serum (AS) eye drops used in a hospital inpatient setting. Method: 14 patients received autologous serum drops from 4 to 14 days with a cumulative total of 67 days. For each day the first and last drop (total 134 samples) was cultured on broth and blood agar. Results: Four patients (9 samples) grew Staphylococcus epidermidis only. One patient (1 sample) showed Staphylococcus epidermidis and a scanty growth of viridans streptococci in the same sample, and on different days the same patient grew Staphylococcus aureus in one sample and Staphylococcus epidermidis in another sample. One patient (1 sample) grew micrococcus. There was no clinical or microbial evidence of infection in any of these six patients Conclusion: This study shows that autologous serum drops can be safely used in an inpatient setting, under a strict protocol of preparation and storage, without significant risk of bacterial contamination and consequent infection.